2019
DOI: 10.1186/s40425-019-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

Severe early hepatitis B reactivation in a patient receiving anti-CD19 and anti-CD22 CAR T cells for the treatment of diffuse large B-cell lymphoma

Abstract: BackgroundHepatitis B virus (HBV) reactivation is commonly seen in HBsAg-positive hematologic patients undergoing immunosuppressive chemotherapy. Little is known about the risk of HBV reactivation after chimeric antigen receptor T-cell (CAR T) immunotherapy for the treatment of refractory/relapsed malignant B-cell lymphoma.Case presentationWe report a patient who underwent antiviral prophylaxis for 26 months and who discontinued treatment by herself 1 month after the sequential infusion of two specific, third-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…This small case study has several important clinical implications: first, together with our previous report of fatal HBV reactivation and clearance failure post anti-CD19/22 CAR T-cell therapy, 23 we confirmed that the absence of humoral immunity can lead to a fatal virus clearance failure and aberrant T-cell activation. As the global COVID-19 pandemic continues, any decision to proceed with immunotherapy such as CAR T-cell therapy or anti-CD20-targeted therapy will require extensive discussion around the potential risks and benefits.…”
Section: Discussionsupporting
confidence: 81%
“…This small case study has several important clinical implications: first, together with our previous report of fatal HBV reactivation and clearance failure post anti-CD19/22 CAR T-cell therapy, 23 we confirmed that the absence of humoral immunity can lead to a fatal virus clearance failure and aberrant T-cell activation. As the global COVID-19 pandemic continues, any decision to proceed with immunotherapy such as CAR T-cell therapy or anti-CD20-targeted therapy will require extensive discussion around the potential risks and benefits.…”
Section: Discussionsupporting
confidence: 81%
“…These results indicate that CAR-T cells can safely and effectively be used to treat patients who were HBV-infected under the protection of anti-HBV drugs, even patients who were HBsAg positive. Wei J et al 37 reported that a patient who had HBsAg-positive DLBCL died of HBV reactivation during CAR-T cell therapy because the patient discontinued antiviral drugs, suggesting the importance of concomitant antiviral and CAR-T cell therapy in patients with cancer who were HBV-infected.…”
Section: Discussionmentioning
confidence: 99%
“…The Stanford University School of Medicine and the National Cancer Institute have launched a phase I clinical trial of anti-CD22 CAR T-cell therapy in patients with relapsed B-cell ALL and obtained significant progress. This includes CD-22 CAR that can mediate similar potent antineoplastic effects as CD19, while the dual CD19/CD22 targeted immunotherapeutic plays an important role to overcome the resistance to immunotherapy via antigen loss (41). In November 2019, Tongji Hospital Affiliated to Tongji Medical College of Huazhong University of Science and Technology (Wuhan, China) published a single case report of HBV reactivation after sequential treatment with CD19 and CD22 in a patient with DLBCL; after 2.5 months of CAR T-cell treatment, the tumor condition remained stable and superficial lymph nodes could not be detected (42).…”
Section: Discussionmentioning
confidence: 99%